Development and function of natural TCR+ CD8αα+ intraepithelial lymphocytes - Gui, Yuanyuan; Cheng, Hao; Zhou, Jingyang; Xu, Hao; Han, Jiajia; Zhang, Dunfang (Frontiers in Immunology, 2022)
The complexity of intestinal homeostasis results from the ability of the intestinal epithelium to absorb nutrients, harbor multiple external and internal antigens, and accommodate diverse immune cells. Intestinal intraepithelial lymphocytes (IELs) are a unique cell population embedded within the intestinal epithelial layer, contributing to the formation of the mucosal epithelial barrier and serving as a first-line defense against microbial invasion. TCRαβ+ CD4- CD8αα+ CD8αβ- and TCRγδ+ CD4- CD8αα+ CD8αβ- IELs are the two predominant subsets of natural IELs. These cells play an essential role in various intestinal diseases, such as infections and inflammatory diseases, and act as immune regulators in the gut. However, their developmental and functional patterns are extremely distinct, and the mechanisms underlying their development and migration to the intestine are not fully understood. One example is that Bcl-2 promotes the survival of thymic precursors of IELs. Mature TCRαβ+ CD4- CD8αα+ CD8αβ- IELs seem to be involved in immune regulation, while TCRγδ+ CD4- CD8αα+ CD8αβ- IELs might be involved in immune surveillance by promoting homeostasis of host microbiota, protecting and restoring the integrity of mucosal epithelium, inhibiting microbiota invasion, and limiting excessive inflammation. In this review, we elucidated and organized effectively the functions and development of these cells to guide future studies in this field. We also discussed key scientific questions that need to be addressed in this area.